Social and ecological factors associated with the use of non-timber forest products by people in rural Borneo. (December 2016) - Sakai, Shoko; Choy, Yee Keong; Kishimoto-Yamada, Keiko; Takano, Kohei T.; Ichikawa, Masahiro; Samejima, Hiromitsu; Kato, Yumi; Soda, Ryoji; Ushio, Masayuki; Saizen, Izuru; Nakashizuka, Tohru; Itioka, Takao
Abstract: Supply of non-timber Forest Products (NTFPs) is an important provisioning ecosystem service. It is often argued that forest conservation contributes to poverty alleviation through provisioning of NTFPs to the poor. However, implicit assumptions of the argument that NTFPs are more intensively utilized by poor who lack alternative subsistence options, and that NTFP supplies are limited by forest cover, have rarely been critically examined. This study investigated social and environmental factors affecting NTFP uses in rural areas of Borneo, using a land cover map and socio-economic dataset collected from 1596 households in 87 villages. The NTFPs examined were wild boars, sambar deer, wild fruits, firewood, wild vegetables, and wild mushrooms. To explain the variations in NTFP uses among households, four village and nine household characteristics were considered using generalized linear mixed models. We found that forest cover and collection pressure limit the use of some NTFPs, supporting the second assumption. On the other hand, the first assumption was supported only for firewood, and animals and wild fruits were more frequently used by wealthier households, contrary to this assumption. Other factors (education, age and sex of householder and agricultural activities) were also related to the use of one or more NTFPs. This study demonstrates the complexity of the process by which forest cover and other factors affect the ecosystem services people receive. Evaluation of ecosystem services is an important and urgent research subject today, but it is also necessary to pay attention to who receives the benefits, and who does not. Highlights: Forest cover was an important but not a predominant factor for the use of NTFPs. The scale and direction of social factors' effects differed among the NTFPs. Contribution of forests to poverty alleviation though NTFPs is minor at present.